2013
DOI: 10.1371/journal.pone.0082148
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a New Electrode Array Technology for a Central Auditory Prosthesis

Abstract: Ongoing clinical studies on patients recently implanted with the auditory midbrain implant (AMI) into the inferior colliculus (IC) for hearing restoration have shown that these patients do not achieve performance levels comparable to cochlear implant patients. The AMI consists of a single-shank array (20 electrodes) for stimulation along the tonotopic axis of the IC. Recent findings suggest that one major limitation in AMI performance is the inability to sufficiently activate neurons across the three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A possible alternative for some of these patients is the auditory midbrain implant (AMI), which targets the central nucleus of the inferior colliculus with a penetrating electrode array (Lenarz et al 2006, Calixto et al 2013, Stebbings et al 2014. However performance with these devices varies dramatically across patients depending on the implant location within the midbrain with the best performance still not able to achieve open set speech perception without lipreading cues.…”
Section: Stimulation Of Auditory Pathway For Restoration Of Hearingmentioning
confidence: 99%
“…A possible alternative for some of these patients is the auditory midbrain implant (AMI), which targets the central nucleus of the inferior colliculus with a penetrating electrode array (Lenarz et al 2006, Calixto et al 2013, Stebbings et al 2014. However performance with these devices varies dramatically across patients depending on the implant location within the midbrain with the best performance still not able to achieve open set speech perception without lipreading cues.…”
Section: Stimulation Of Auditory Pathway For Restoration Of Hearingmentioning
confidence: 99%
“…The two main dominant approaches are multiple insulated metal microwires (Nicolelis and Lebedev, 2009 ; Freire et al, 2011 ; Carmena, 2013 ) and penetrating microelectrode arrays fabricated with micro-electro-mechanical-system technologies. These devices use various substrate materials that can either be flexible and based on polymers (Rousche et al, 2001 ; Chen et al, 2009 ; Kozai and Kipke, 2009 ; Hassler et al, 2011 ) or rigid such as the Utah Electrode Array (UEA; Normann, 2007 ), the Michigan array (Seymour and Kipke, 2007 ) or the NeuroProbes arrays (Neves, 2007 ; Calixto et al, 2013 ). However today, only a few of these devices are commercially available and do not yet exist as commercial, wireless, implantable, many-channel devices that can provide reliable recording and stimulation for many years.…”
Section: Current Multielectrode-array Technologiesmentioning
confidence: 99%
“…In a recent neurophysiological work [35] carried out with the same 3D electrode arrays as used in this study and in an earlier report using similar probes [47], it has been shown that the probe technology can also be used for intracortical electrical microstimulation. This additional functionality further expands the potential versatility of the reported stacking system.…”
Section: Discussionmentioning
confidence: 77%